HYDRANENCEPHALY IN A PRIMIGRAVIDA - Taher, M. Abu (The ASEAN Journal of Radiology, 2023)
A case of hydranencephaly in a primigravid woman seen in our centre by ultrasonography is presented considering its rarity.